Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s00344-021-10428-w
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide as a Key Gasotransmitter in Fruit Postharvest: An Overview

Abstract: Currently, the field of postharvest technology is a growing research area of particular interest since the increase in world population and the need to satisfy its nutritional requirements. These aspects establish a demand to produce fruits with high market quality while minimizing the losses from production to consumption stages. In the past few years, nitric oxide (NO) has emerged as a novel gasotransmitter to improve fruit postharvest shelf-life, owing to its influence on physiological processes (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 124 publications
(210 reference statements)
1
7
0
Order By: Relevance
“…NO treatment has been shown to improve sugar accumulation and limit anthocyanin degradation [ 8 , 12 , 13 , 14 ], which supports our strategy to improve the quality of blood orange fruit by NO treatments on living blood orange trees. In addition, the mechanisms by which NO improves fruit flavors were further explored in this study.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…NO treatment has been shown to improve sugar accumulation and limit anthocyanin degradation [ 8 , 12 , 13 , 14 ], which supports our strategy to improve the quality of blood orange fruit by NO treatments on living blood orange trees. In addition, the mechanisms by which NO improves fruit flavors were further explored in this study.…”
Section: Introductionsupporting
confidence: 65%
“…Nitric oxide (NO) is a highly active substance that acts as an antioxidant and biological messenger in plant systems. NO is a signal molecule with multiple functions, such as regulating flowering transition [ 6 ], promoting photosynthesis [ 7 ], and participating in fruit ripening [ 8 , 9 ]. The fruit ripening process is related to reactive oxygen species (ROS) production and increased lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al (2014) observed that NO pretreatment at 22°C reduced oxidative stress and chill damage in bananas stored at 7°C. The effect of NO depends on its concentration, the fruit species (Manjunatha et al, 2010), and the time of exposure to the gas (Buet et al, 2021). There are no studies evaluating the effect of NO on the ripening delay and oxidative stress of bananas in CA storage conditions.…”
mentioning
confidence: 99%